Knock Out of S1P3 Receptor Signaling Attenuates Inflammation and Fibrosis in Bleomycin-Induced Lung Injury Mice Model - Murakami, Ken (Public Library of Science, 2014)
Sphingosine-1-phosphate (S1P) is a bioactive sphingolipid metabolite involved in many critical cellular processes, including proliferation, migration, and angiogenesis, through interaction with a family of five G protein–coupled receptors (S1P1–5). Some reports have implicated S1P as an important inflammatory mediator of the pathogenesis of airway inflammation, but the role of S1P3 in the pathogenesis of lung diseases is not completely understood. We used S1P3-deficient (knockout (KO)) mice to clarify the role of S1P3 receptor signaling in the pathogenesis of pulmonary inflammation and fibrosis using a bleomycin-induced model of lung injury. On the seventh day after bleomycin administration, S1P3 KO mice exhibited significantly less body weight loss and pulmonary inflammation than wild-type (WT) mice. On the 28th day, there was less pulmonary fibrosis in S1P3 KO mice than in WT mice. S1P3 KO mice demonstrated a 56% reduction in total cell count in bronchoalveolar lavage fluid (BALF) collected on the seventh day compared with WT mice; however, the differential white blood cell profiles were similar. BALF analysis on the seventh day showed that connective tissue growth factor (CTGF) levels were significantly decreased in S1P3 KO mice compared with WT mice, although no differences were observed in monocyte chemotactic protein-1 (MCP-1) or transforming growth factor β1 (TGF-β1) levels. Finally, S1P levels in BALF collected on the 7th day after treatment were not significantly different between WT and S1P3 KO mice. Our results indicate that S1P3 receptor signaling plays an important role in pulmonary inflammation and fibrosis and that this signaling occurs via CTGF expression. This suggests that this pathway might be a therapeutic target for pulmonary fibrosis.